Long-Term Survival After Coronary Artery Bypass Graft Surgery - Vyas, Charu; Wang, Pengchen; Sun, Jocelyn; Logan, Rachel; Smith, Cindy; Guderian, Emily; Schnell, Susan; Argenziano, Michael; Kurlansky, Paul (The Annals of thoracic surgery, 2025)
Management guidelines for stable 3-vessel coronary artery disease have become a subject of debate. We aim to provide a benchmark for the survival of patients with normal ejection fraction, stable 3-vessel disease, and elective coronary artery bypass graft (CABG) surgery. Data from consecutive patients with normal ejection fraction undergoing elective primary isolated CABG for 3-vessel disease in a diverse 11-center surgical network between 2008 and 2020 were analyzed. Survival data were obtained from the Centers for Disease Control and Prevention National Death Index and compared with an age- and sex-matched United States population. Mixed-effects modeling with “hospital” as a random effect was used to evaluate factors associated with all-cause mortality. Of 4061 patients included in this analysis, 893 (22%) were women, and the median age was 68 years (interquartile range, 61-74 years). Patients with elective CABG surgery for 3-vessel disease and normal ejection fraction demonstrated improved survival compared with an age- and sex-matched United States population, with significantly increasing relative survival over time. Factors associated with mortality included age ≥65 years (hazard ratio [HR], 1.71; P < .001), male sex (HR, 1.32; P = .028), diabetes (HR, 1.4; P = .002), dialysis (HR, 2.41; P = .03), moderate or severe chronic lung disease (HR, 1.68; P < .001), and peripheral arterial disease (HR, 2.05; P < .001). Patients with stable 3-vessel disease and normal ejection fraction who underwent elective CABG demonstrated improved survival compared with an age- and sex-matched United States population. With this benchmark, further research can better elucidate the relative role of surgery and medical therapy in this patient population. [Display omitted]